The environmental deterioration and its effects on the tourist activity in Lattakia region - خضرة, جلال; بت ولاد, وهيبه (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
Lattakia region suffers from environmental deterioration caused by several weak points in rules, the weakness of the environmental culture and the oppressive use of the natural resources without caring about the negative effects which humans impose on their environmental. In addition to that there are a lot of reasons like what the terrorists groups have done like burning and deteriorating the natural resources which lead to put down the natural quality and the increase the levels of the environmental deterioration especially in forests. Tourism is considered one of the human activities which is greatly affected by environmental natural features because the environment defines the patterns, centers, the distribution of the tourist sites and the amount of tourists movement. According to this, the environmental deterioration in Lattakia region has affected the tourist activity negatively in it. This research takes in consideration the environmental deterioration reasons in the region and its effects on the tourist activity in it and the attempt to solve it to make tourism lasts.